PENERAPAN HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA PENIPUAN ONLINE MELALUI LINK PHISHING DOWNLOAD APK (ANDROID PACKAGE KIT) - NIM. A1011211022, MICHAEL FREDERICK (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The development of technology and an increasingly modern era today brings various positive things to people's lives, but this has also led to the emergence of crimes in the field of technology or cybercrime with new, more modern modes, such as Online Fraud Through Phishing Link Download APK File (Android Package Kit). If this is not followed by the design and formulation of a legal provision, it can result in uncertainty in law enforcement and ambiguity in the application of an article to the criminal offense.Therefore, the author formulates the problems that become the main discussion in this study, namely: